What works? A qualitative study of participants experiences of a traditional lifestyle intervention with a work focus. Issue 1 (31st December 2022) - Andersen, Wivi; Linge, Anita Dyb; Jensen, Chris
ABSTRACT: Purpose: Obesity is related to lower labour force participation, increased sickness absence and reduced productivity. The rehabilitation services in Norway have not had much experience introducing a work dimension into lifestyle interventions for persons with obesity. Therefore, this study aimed to evaluate one such type of intervention. Methods: This is a qualitative study seeking to gather data on the participants' experiences. Twenty participants were recruited from two lifestyle interventions. Intervention A, with work focus, included lectures and individual guidance from a work consultant in addition to the lifestyle intervention. Intervention B was a traditional lifestyle intervention. Data were collected by semi-structured interviews held at each stay. Results: Seven main themes emerged and one of them pointed towards a confusion of the aim of the intervention, which was viewed as focusing on lifestyle rather than a process focused on work. Otherwise, the results showed that persons with obesity struggle with many of the same inhibiting factors as other groups with reduced work ability. Conclusions: The application process might explain the focus on lifestyle change. Communication, guidance and support reduce barriers for lifestyle change, but work is important for general health and social well-being and a work focus may therefore be beneficial in all lifestyle interventions.